Mekanisme Corporate Governance dan Pengungkapan Informasi Covid-19 - Azmiyanti, Rizdina; Fahriza, Taris Anggie; Sabrina, Marthaza; Widoretno, Astrini Aning (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
This study aims to examine the effect of independent commissioners, size of directors, and gender diversity of directors on disclosure of COVID-19 information. The population of this study are banking companies listed on the Indonesia Stock Exchange totaling 46 companies. Sampling used a purposive sampling method with criteria, namely banking companies that publish annual reports in 2020-2021 which contain the data needed by researchers, so that those selected as samples were 39 companies. The method used in analyzing the data is multiple linear regression. The results of the study show that independent commissioners have a significant positive effect on disclosing covid-19 information, while the size of directors and the gender diversity of directors have no effect on disclosing covid-19 information. Independent commissioners, size of directors, and gender diversity of directors simultaneously have a significant effect on disclosure of COVID-19 information. The research proves that directors tend tnot to disclose risky information for company.